Pengaruh Kepemimpinan Terhadap Kinerja Melalui Motivasi Instrinsik Pada Bank Artha Graha Pekanbaru - Jonison '; Samsir '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at the International Tbk Bank Artha Graha Pekanbaru in order to determine and analyze the effect of leadership on employee performance through intrinsic motivation. Research has a population of 107 employees of Bank Artha Graha Pekanbaru International Tbk and using census sampling to take the number of samples 107 employees. The analytical method used is descriptive analysis method is a way to test variables, regression testing, and final test path analysis or path analysis. From the results of the testing that has been done, there is a direct effect between leadership variables on intrinsic motivation. Intrinsic motivation has a positive effect on employee performance, which means the employee's performance is influenced by intrinsic motivation. And for leadership to employee performance variables terdpat positive influence employee performance means influenced by leadership. For the indirect effect, namely, the influence of leadership on employee performance through intrinsic motivation to get the positive effects. From the results, the relationship is directly influence the effect of a positive effect, but the effect of leadership on performance through intrinsic motivation effect is smaller when compared to the effect directly. Bank Artha Graha Pekanbaru should be more attention in improving the performance of employees, Bank Artha Graha management should conduct continuous evaluation to employees to be able to perform two way communication in order to obtain in depth information about the employee's performance problems.Keywords: Leadership, intrinsic motivation and employee performance